A system to administer an outcome based education. - Jaafar, Mohd Saleh; Megat Mohd Noor, Megat Johari; Noordin, Nor Kamariah; Wagiran, Rahman; Abdul Aziz, Azlan; Osman, Mohd. Rasid; Abu Talib, Abd. Rahim (2010)

(untitled)
The present invention relates to a system to administer an outcome based education for higher learning academic programs, the system includes (a) at least one design process (100), wherein the design process (100)encompasses planning structure for achieving required learning outcomes, (b) at least one implementation process (200) to control the planning structure of the design process (100) (c) at least one assessment process (300) to evaluate results of the implementation process (200) wherein results of assessment of the design, implementation and assessment processes are integrated into a database system which is made available for consideration in continual quality improvement (CQI) of an academic program; and wherein implementation of the system enables to monitor complete cycle of design, implementation, assessment, and continual quality improvement processes.